2013
DOI: 10.1371/journal.pone.0060144
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Commonly Used Transplant Immunosuppressive Drugs on Human NK Cell Function Is Dependent upon Stimulation Condition

Abstract: Lung transplantation is a recognised treatment for patients with end stage pulmonary disease. Transplant recipients receive life-long administration of immunosuppressive drugs that target T cell mediated graft rejection. However little is known of the impact on NK cells, which have the potential to be alloreactive in response to HLA-mismatched ligands on the lung allograft and in doing so, may impact negatively on allograft survival. NK cells from 20 healthy controls were assessed in response to Cyclosporine A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…Indeed, CsA pharmacodynamic effect on NK cells is distinct and allows NK cell cytotoxicity, 41 whereas it is impaired by MMF [42][43][44] or MTX. [45][46][47] Moreover, calcineurin inhibitors are the only immunosuppressive agents exerting their action by inhibiting interleukin-2 production.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CsA pharmacodynamic effect on NK cells is distinct and allows NK cell cytotoxicity, 41 whereas it is impaired by MMF [42][43][44] or MTX. [45][46][47] Moreover, calcineurin inhibitors are the only immunosuppressive agents exerting their action by inhibiting interleukin-2 production.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are contradictory reports in the literature [45e47]. It can be suggested that NK cell stimulation occurs through multiple pathways of intracellular activation (including protein kinase C and calcineurin pathways) [48]. The potent inhibitory effects of mycophenolate mofetil (MMF) on NK cell proliferation and cytotoxic activity are apparently more evident than those of other immunosuppressants, including CsA, tacrolimus and methotrexate [49] The NK-activating receptor expression of NK cells is downregulated by MMF, and the inhibitory effect is partially abrogated.…”
Section: Discussionmentioning
confidence: 99%
“…PMA and Io are routinely used to establish a T cell receptor-independent model to study T cell activation and proliferation [14]. By mimicking the phospholipase C-driven activation of PKC and the increase of cytosolic Ca 2+ , PMA and Io activate the transcription factors NFAT1, NF-κB and activator protein-1 (AP-1), and subsequently regulate downstream gene expression [38].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that factors activating NFAT1, such as phorbol myristate acetate (PMA) and ionomycin (Io), will further influence GBM cell growth. The combination of PMA and Io has been widely used in the study of T cell activation [11], [12], [13], [14]. Through activation of protein kinase C (PKC) and calcineurin, PMA/Io can activate many transcription factors, including NF-κB and members of the NFAT family, and subsequently regulate the expression of numerous genes [13].…”
Section: Introductionmentioning
confidence: 99%